SEAGRESS COVERAGE AND ECOSYSTEM CONDITION AT THE COASTAL AREA OF MADASANGER, JELENGA AND MALUK, WEST SUMBAWA - Erny Poedjirahajoe; Ni Putu Diana Mahayani; Boy Rahardjo Sidharta; Muhamad Salamuddin (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
The increase of temperature might affect the distribution and reproduction of seagrass. This research aims to determine the seagrass bed coverage and the ecosystem condition. Three line transects were established perpendicular to the coastal line with the distance of 50-100 m, or up to the border of the intertidal area. In each transect, sampling points were determined with a distance of 10-20 m. At the sampling points, a plot of 50 cm x 50 cm was established to measure the coverage percentage of seagrass vegetation. The seagrass species were also observed and recorded along the line transects. The percentage of seagrass coverage was measured using a method from Saito and Atobe (1994). The results showed that the coastal area of Jelenga has the highest percentage of seagrass coverage (>60%, healthy) among other coastal areas. This may be caused by the characteristic of Jelenga coast which was relatively calm, few visitors, low water turbidity, and high light penetration. While, other transects have percentage coverage of less than 60% (less healthy). There was one transect on Maluk coast which has coverage percentage of less than 29% (lack of seagrass species). The small coverage percentage on Maluk coast can be caused by the high number of visitors and high activity of fishing boats around the coast which results in high turbidity. Keywords: coverage, ecosystem condition, seagrass bed, west Sumbawa.